2009
DOI: 10.1152/ajpheart.00049.2009
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia and reperfusion injury is dependent on both IgM and mannose-binding lectin

Abstract: Complement activation has been shown to play an important role in the inflammation and tissue injury following myocardial ischemia and reperfusion (MI/R). Several recent studies from our laboratory demonstrated the importance of mannose-binding lectin (MBL) as the initiation pathway for complement activation and the resulting pathological effects following MI/R. However, other studies from the past suggest an important role of the classical pathway and perhaps natural antibodies. In the present study, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 33 publications
5
51
1
Order By: Relevance
“…Similar results were obtained in the myocardial model of I/R (MI/R), where the sIgM/MBL KO mice were investigated in an analogous plasma reconstitution mouse model of MI/R (Busche et al, 2009). Echocardiography showed that both MBL and IgM were required for MI/R-induced loss of left ventricular function.…”
Section: Mbl Is a Risk Factor For Tissue Injurysupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results were obtained in the myocardial model of I/R (MI/R), where the sIgM/MBL KO mice were investigated in an analogous plasma reconstitution mouse model of MI/R (Busche et al, 2009). Echocardiography showed that both MBL and IgM were required for MI/R-induced loss of left ventricular function.…”
Section: Mbl Is a Risk Factor For Tissue Injurysupporting
confidence: 67%
“…During the past decade, in vivo studies of MBL null mice have shown that MBL-deficiency is protective in I/R injuries in heart (Walsh et al, 2005;Busche et al, 2009), kidney (Moller-Kristensen et al, 2005), gut (Hart et al, 2005;Zhang et al, 2006;McMullen et al, 2006), skeletal muscle (Chan et al, 2006) and brain (Cervera et al, 2010;de la Rosa et al, 2014).…”
Section: Mbl Is a Risk Factor For Tissue Injurymentioning
confidence: 99%
“…Although classical pathway activation cannot be excluded, our findings of increased C4bc is in accordance with lectin pathway activation during the acute phase,33, 42 although the role of the lectin pathway in post‐MI HF is still elusive.…”
Section: Discussionsupporting
confidence: 82%
“…Particularly, the lectin pathway has been linked to complement‐mediated myocardial injury and HF,18, 33, 34, 35 and lectin pathway recognition molecules were therefore thoroughly investigated in the present study. MBL and the ficolins are circulating recognition molecules binding to molecular structures on damaged host cells further activating the mannose‐binding serine proteases, MASP1 and MASP2 36.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have emphasized the interaction of IgM with MBL resulting in activation of the lectin pathway [16]. Myocardial and gastrointestinal models in MBL knockout mice have shown both IgM and MBL to be essential for generation of tissue damage [17,18]. Studies in rat intestinal I/R and in patients with myocardial infarcts have also suggested a role for CRP in local complement activation [19,20].…”
Section: Introductionmentioning
confidence: 99%